ANALISIS PENGARUH KORUPSI TERHADAP AUDIT PEMERINTAHAN PADA INSTANSI PEMERINTAH DI INDONESIA - La Ode Ibnu Hafidz Saleh; Dwi Ratmono (Diponegoro Journal of Accounting, 2017)
This research aims to analyze the influence of corruption on government audit in government institution in Indonesia. The Independent variables that are tested in this study are corruption and the dependent variable is audit irregularities and audit opinion, with real expenditure and asset as control variable. This study uses secondary data derived from audit report of Badan Pemeriksa Keuangan in ministries of Indonesia and annual report of Komisi Pemberantasan Korupsi. The research object is 33 ministries of central government for 4 years in 2010-2013. The analytical method used is multiple linear regression analysis and ordinal logistic regression analysis. The results show that corruption have significantly positive effect on audit irregularities detected by BPK RI. However, corruption does not affect audit opinion.